Inventory of Archaic Vocabulary in the Asilulu Language as an Effort to Preserve Regional Language Among Parents - Mamang, Abdul Gani; Rumalean, Iwan (Universitas Pattimura, 2025)
This study seeks to document archaic vocabulary to conserve regional language among parents in the Assilulu language of Leihitu District, Central Maluku Regency, Maluku Province. This study employs a descriptive qualitative methodology. The data gathering methods employed in this instance are observation, interviews, and documentation. This study was conducted in Astilulu Village, Leihitu District, Central Maluku Regency. Assilulu Village in Leihitu District was selected due to the predominant use of the Asailulu language among its population. This research functions as a data collection effort utilizing the primary instrument, which is actively engaged in data gathering. The researcher’s direct presence in the field acts as a criterion for the effective comprehension of concerns pertaining to the inventory of archaic vocabulary in the Assilulu language. Analysis of the collected data revealed that archaic vocabulary from the Assilulu language is predominantly utilized by the elderly. Specifically, the term Yami is infrequently encountered, as the term Ami, meaning